Certain subclasses of multivalent close-to-convex functions associated with generalized Janowski functions - Singh, Gagandeep; Singh, Gurcharanjit (Sarajevo Journal of Mathematics, 2025)
Close-to-convex functions have a great importance in the field of Geometric function theory. Many researchers of this field have extensively established various subclasses of close-to-convex univalent functions and studied certain important properties of these subclasses. In this paper, we introduce a generalized subclass of multivalent close-to-convex functions in the open unit disc. We investigate several properties such as coefficient estimates, inclusion relation, distortion theorem,argument theorem and an important result for the defined class. Many known results follow as consequences of the results derived in this paper.